Promoting social partnership in empolyee training : final report - Flake, Regina [Verfasser]; Seyda, Susanne [Verfasser]; Zibrowius, Michael [Verfasser] (Institut der deutschen Wirtschaft Köln, 2018)
Facing fast-changing labour market demands, employers have a rising need for an adequately qualified workforce. In the wake of global trends like the digitalisation of the economy, employees are faced not only with higher demands for competences but also with the requirement to continuously adapt and further develop their skills to maintain their employability. In countries in which the demographic change leads to a rapid ageing and a shrinking workforce, lifelong learning becomes even more important for individuals to remain employable at higher ages. It is important to bring together individual needs regarding the personal, social and professional development with general labour market and business demands. An important result of the cross-country comparison is that in all countries, employers and employees need support regarding provision of and participation in employee training, and that social partners are key actors in this regard. It could be shown that a general lack of financial resources is often not the main obstacle to training. It is more challenging to provide support in the form of additional information and guidance for specific target groups like low-skilled employees or small and medium-sized enterprises (SMEs). In addition, time restrictions are an important obstacle, in particular when the economy is booming and the order books are full." (Excerpt, BIBB-Doku)
Keywords: S 1.5.2 Berufliche Weiterbildung; G 2.2.4 Lebensbegleitendes & lebenslanges Lernen; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; S 3.5.4 Sozialpartner; Berufliche Weiterbildung; Lebenslanges Lernen; Weiterbildungsbeteiligung; Weiterbildungsbedarf; Internationaler Vergleich